2022
DOI: 10.1155/2022/7278064
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Curcumin Gel in Experimental Induced Diabetes and Periodontitis in Rats

Abstract: This study aimed to evaluate the effect of curcumin gel on antioxidant marker level in experimental induced diabetes and periodontitis (EDP) in rats. Adult Wistar rats were randomized into five groups (20 each): (1) EDP treated with scaling and root planing (SRP) + curcumin gel (CU), (2) EDP treated with CU, (3) EDP treated with SRP, (4) EDP without treatment, and (5) systemically healthy and without ligature (control). Each group was subdivided equally into 4 subgroups of 5 rats. Diabetes was induced by intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…It has been investigated for the treatment of minor recurrent aphthous stomatitis (RAS) and oral leukoplakia and as an adjunct in endodontic therapy, gingivitis treatment, and oral wound healing. Additionally, curcumin gel shows potential as an adjunctive therapy in periodontal treatment [ 92 , 93 , 94 , 96 , 97 , 99 , 104 , 116 , 117 , 118 ], reducing bone and root resorption during orthodontic treatment and enhancing the efficacy of scaling and root planing (SRP) in treating chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been investigated for the treatment of minor recurrent aphthous stomatitis (RAS) and oral leukoplakia and as an adjunct in endodontic therapy, gingivitis treatment, and oral wound healing. Additionally, curcumin gel shows potential as an adjunctive therapy in periodontal treatment [ 92 , 93 , 94 , 96 , 97 , 99 , 104 , 116 , 117 , 118 ], reducing bone and root resorption during orthodontic treatment and enhancing the efficacy of scaling and root planing (SRP) in treating chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing outcomes of periodontal therapy, anti-inflammatory properties [89] Adjunctive use of curcumin gel with SRP Improved outcomes in chronic periodontitis, potential complementary treatment [90] Adjunctive use of curcumin oral gel Effective improvement in periodontal pocket parameters [34] 2% curcumin gel Effective treatment of experimental periodontitis [91] Comparison of chlorhexidine gel and curcumin gel Both gels as adjuncts to scaling and root planing, curcumin as an alternative [93] Curcumin gel as an adjunct to scaling and root planing Limited additional benefits in reducing gingival inflammation [95] Curcumin gel and noneugenol periodontal dressing for post-surgery treatment Effectiveness in reducing tissue edema and promoting wound healing [96] Curcumin gel injection with scaling and root planing Reduction of clinical parameters and inflammatory mediators [97] Scaling and root planing combined with curcumin Comparable results to tetracycline in reducing inflammation and bone resorption [98] Curcumin gel as an adjunct to SRP in diabetes-induced periodontitis Reducing oxidative stress and improving antioxidant enzyme levels [99] In situ gel formulation of curcumin Effective treatment of periodontal pockets [35] Curcumin + carbopol gel + LED curing light Alternative to conventional photodynamic therapy for root canal disinfection [32] Split-mouth design study with curcumin gel Potential adjunct to nonsurgical periodontal therapy [94] Evaluation of curcumin's antibacterial activity against P. gingivalis Effective antibacterial action at low concentrations [92] Curcumin gel in experimental periodontitis using Wistar rats Effective in treating experimental periodontitis and preventing bone destruction [116] Clinical trial evaluating subgingival delivery of curcumin gel as an adjunct to SRP Effective anti-inflammatory and antibacterial properties, alternative to chlorhexidine [117] Clinical trial comparing scaling and root planing alone, curcumin application, and curcumin photodynamic therapy Curcumin photodynamic therapy as an adjunct to scaling and root planing improves treatment outcomes [118] Oral Submucous Fibrosis (OSMF) Management…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In diabetes associated with periodontitis, a modified form of Cu seems to have anti-inflammatory effects and improvement of diabetic osteoporosis, even in maintained hyperglycemic conditions [24]. Administered locally curcumin showed a reduction of the oxidative stress biomarker, malondialdehyde, and antioxidant enzymes amending periodontitis in diabetic rats [25]. Periodontal pathogenic microorganisms were inhibited by topically applied Cu.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin (Cur) is a polyphenol that can be isolated from samples of turmeric root [ 1 ]. Prior research has demonstrated that Cur possesses a range of anti-tumor [ 2 , 3 ], anti-cancer [ 4 , 5 ], anti-inflammatory [ 6 ], antioxidant [ 7 ], and anti-ischemic [ 8 ] pharmacological properties. In the context of tumor treatment, Cur has been shown to be capable of inducing apoptotic tumor cell death inhibiting the proliferative and invasive activity of these cells [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%